THE LEVEL AND QUALITY OF INCLUSIVE GROWTH AGRI-FOOD SYSTEM IN MODERN CONDITIONS - Elena DERUNOVA; Natal’ya KIREEVA; Olesya PRUSCHAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
With regard to the agri-food system, the theoretical and methodological basis for the study of inclusive development has been substantiated. The study reveals the concept of inclusive development of the agri-food system, substantiates criteria and indicators, and proposes assessment methods. New risks associated with the COVID-19 pandemic are analyzed in the development of the agro-food system, which has aggravated the existing systemic problems and negatively affected the quality of life of Russians. A comparative analysis of the quality of inclusive development of the agri-food systems of the Saratov region and Russia in the context of the main blocks: growth and development, the fairness of distribution of public goods between all strata and groups of the population, the involvement of all forms of management, food security, environmental sustainability. An integral indicator of the level and quality of inclusive development of the agri-food system of Russia and the Saratov region was calculated. Measures are formulated to facilitate the transition of the agri-food system to an inclusive development model and overcome negative trends in the post-pandemic economy.